A Water‐Gated Organic Thin‐Film Transistor for Glyphosate Detection: A Comparative Study with Fluorescence Sensing. Issue 64 (12th October 2020) - Sasaki, Yui; Asano, Koichiro; Minamiki, Tsukuru; Zhang, Zhoujie; Takizawa, Shin‐ya; Kubota, Riku; Minami, Tsuyoshi
Abstract: This work reports the design of a highly sensitive solid‐state sensor device based on a water‐gated organic thin‐film transistor (WG‐OTFT) for the selective detection of herbicide glyphosate (GlyP) in water. A competitive assay among carboxylate‐functionalized polythiophene, Cu 2+, and GlyP was employed as a sensing mechanism. Molecular recognition phenomena and electrical double layer (EDL) (at the polymer/water interface) originated from the field‐effect worked cooperatively to amplify the sensitivity for GlyP. The limit of detection of WG‐OTFT (0.26 ppm) was lower than that of a fluorescence sensor chip (0.95 ppm) which is the conventional sensing method. In contrast to the previously reported insulated molecular wires to block interchain interactions, molecular aggregates under the field‐effect has shown to be effective for amplification of sensitivity through "intra"‐ and "inter"‐molecular wire effects. The opposite strategy in this study could pave the way for fully utilizing the sensing properties of polymer‐based solid‐state sensor devices. Abstract : A water‐gated organic thin‐film transistor (WG‐OTFT) and a fluorescence sensor chip in the solid state were used in a comparative study that showed higher sensitivity of the WG‐OTFT. The advantage of the WG‐OTFT has been explained by the combination of two types of molecular wire effects under the physical stimuli. This study could lead to "organic electronics in water" based on the WG‐OTFT as a chemical sensing platform.